High-Directivity Antenna Array Based on Artificial Electromagnetic Metamaterials with Low Refractive Index - Zhigang Xiao; Jiang Yao; Shaoquan Yin (International Journal of Antennas and Propagation)
Planar metamaterials (MTMs) with low refractive index are proposed as a cover in a high-gain patch antenna array configuration. This MTMs array antenna has the following features: the number of array elements significantly decreases compared with the conventional array; the elements spacing is larger than a wave length by far; the feeding network is simpler. MTMs are made of two layers of periodic square metallic grids and placed above the feeding array. With the same aperture size, the directivity of MTMs-cover antenna array is higher than the conventional antenna array. The simulation results show that an array of 2 × 2 patch elements integrated with MTMs yields about 26 dB of directivity which is higher than that of conventional 8 × 8 patch array. Furthermore, on the condition of the same aperture size, an array patch with 4 × 4 elements integrated with the MTMs-cover has an equivalent gain compared with the conventional patch array with 16 × 16 array elements. Obviously, the former has a simpler feeding network and higher aperture efficiency. The experimental work has verified that the 2 × 2 array case and the measured results have good agreement with the simulation.